Groin lumps during pregnancy: Exploring the knowledge gap among surgeons and obstetricians regarding round ligament varicosities - Zaid Malaibari; Razaz Aldemyati; Reham H. Alrahil; Shumoukh H. Alshehri; Rahaf H. Alrahil; Ahmed T. Alghabban; Salman A. Alshamrani; Salihah S. Alzubaidi (International Journal of Abdominal Wall and Hernia Surgery)
BACKGROUND: This cross-sectional pilot study aimed to evaluate awareness and management strategies among obstetricians and surgeons in the Kingdom of Saudi Arabia for round ligament varicosities (RLV) during pregnancy. MATERIALS AND METHODS: An online questionnaire was distributed through convenience sampling to surgeons and obstetricians across the Kingdom of Saudi Arabia. It assessed demographics, clinical knowledge, experience in diagnosing and managing groin lumps during pregnancy, and engagement in continuing medical education. RESULTS: Of the 39 participants, 56.41% (n = 22) were obstetricians and 43.59% (n = 17) were surgeons, with the majority having 5–10 years of practice (35.90%, n = 14). Groin hernia was reported as the most frequent diagnosis for groin lumps during pregnancy (43.59%, n = 17), whereas only 7.69% (n = 3) identified RLV, indicating a significant gap in recognizing RLV. Furthermore, 35.90% (n = 14) recognized RLV as a differential diagnosis, but only 25.64% (n = 10) were aware of its management. CONCLUSION: RLV, which is more common than hernias during pregnancy, is often misdiagnosed due to its similar presentation. Accurate differentiation, often achieved through ultrasound, is crucial as management strategies significantly differ. This study underscores the need for enhanced awareness and training among obstetricians and surgeons to accurately diagnose and manage RLV. The observed knowledge gaps highlight the critical role of continuous medical education in improving patient care. These findings will guide a larger study to assess practices across the Kingdom and develop national recommendations for the management of RLV and groin hernias during pregnancy.